Body mass and locomotor habits of the smallest darter, Anhinga minuta (Aves, Anhingidae) - Diederle, Juan Marcelo (2016)
During the Neogene of South America, Anhingidae was represented by several species, mainly with greater sizes than the extant members. In the present contribution, body mass and locomotor habits of Anhinga minuta, the smallest known darter, were inferred. Body mass was estimated using two methods, one with measures of a tibiotarsus (the holotype) and the other, with measurements of a humerus; locomotor habits were inferred through muscular reconstructions and wing parameters (wing span, wing area and wing loading). Estimates of wing span and wing area were based on the length of humerus, assuming a condition of isometry with respect to Anhinga anhinga; wing loading was obtained through a relation formula between wing area and body mass. The results obtained indicate a body mass of about 729 g, a wing span of 0.958 m, a wing area of 0.117 m2 and a corresponding wing loading of 61 N/m2. These values and also the proximal insertion of the musculus pectoralis are consistent with those of a soaring bird but with more frequent flapping than extant anhingids. Furthermore, the inferred musculature for tibiotarsusindicates abilities for swimming, climbing and moving through the vegetation as in extant representatives.